2020
DOI: 10.1016/j.scitotenv.2020.141226
|View full text |Cite
|
Sign up to set email alerts
|

How tropical cyclone flooding caused erosion and dispersal of mercury-contaminated sediment in an urban estuary: The impact of Hurricane Harvey on Buffalo Bayou and the San Jacinto Estuary, Galveston Bay, USA

Abstract: Hurricane Harvey (Harvey), a slow-moving storm, struck the Texas coast as a category 4 hurricane. Over the course of 53 days, the floodwaters of Harvey delivered 14 × 10 9 m 3 of freshwater to Galveston Bay. This resulted in record flooding of Houston bayous and waterways, all of which drained into the San Jacinto Estuary (SJE,) with its main tributaries being Buffalo Bayou and the San Jacinto River. The lower SJE and lower Buffalo Bayou has experienced up to 3m of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…To conclude, this means that the estimated risk for our case study is an underestimation rather than an overestimation, even considering the lower levels of the 90% confidence intervals. It also confirms the importance of taking into account advective dispersion pathways in risk assessments (e.g., Erickson et al, 2005;Davis et al, 2007;Reible, 2014;Howell and Rifai, 2015;Dellapenna et al, 2020).…”
Section: The Case Studysupporting
confidence: 68%
See 2 more Smart Citations
“…To conclude, this means that the estimated risk for our case study is an underestimation rather than an overestimation, even considering the lower levels of the 90% confidence intervals. It also confirms the importance of taking into account advective dispersion pathways in risk assessments (e.g., Erickson et al, 2005;Davis et al, 2007;Reible, 2014;Howell and Rifai, 2015;Dellapenna et al, 2020).…”
Section: The Case Studysupporting
confidence: 68%
“…This outcome is probably also true for many other fiberbank deposits, and for contaminated sediments located in shallow waters (e.g., Butcher and Garvey, 2004;Davis et al, 2007;Howell and Rifai, 2015). Even archived contaminants may become exposed to dispersion because of sediment scouring during extreme weather-events like hurricanes (Dellapenna et al, 2020). Our study also includes the potential for contaminant dispersion from submarine landslides, and the results indicate that a submarine landslide will disperse most contaminants per unit area (i.e., flux), followed by advection through ship induced resuspension, river flow resuspension, wind-wave current resuspension, and least by chemical diffusion.…”
Section: The Case Studymentioning
confidence: 96%
See 1 more Smart Citation
“…For example, surface sediment was measured in Galveston Bay, and it was found that various particle reactive metals (e.g., lead, barium, mercury, copper, manganese, zinc, etc.) and polycyclic aromatic hydrocarbons (PAHs) sorbet onto the sediment, meaning that they have a great chance of resuspending during resuspension events (Santschi et al, 2001;Dellapenna et al, 2020;Camargo et al, 2021). Therefore, our estimated residence time of suspended sediments (51-105 days, Table 2) suggest these pollutants that adsorb to suspended sediment may spend months before they leave the Galveston Bay.…”
Section: Implications To the Galveston Bay Environmentmentioning
confidence: 99%
“…Wind-induced currents and wave resuspension are important sources of energy for sediment transport within an ecosystem and can be dominant in shallow, microtidal estuaries, affecting a large portion, if not all of the water column (Booth et al, 2000). Sediment resuspension associated with strong weather events can reintroduce trace elements and pollutants back into the water column, which can have significant environmental impacts in an estuary (e.g., Dellapenna et al, 2006Dellapenna et al, , 2020. These constituents can be stored in the sediment during periods of sediment deposition and are resuspended during wind-induced wave resuspension, in addition to any other resuspension events (Dellapenna et al, 2006).…”
Section: Introductionmentioning
confidence: 99%